Intensification Strategy For Cost-Effective Hybrid Power System Using Power Pinch Analysis - Rosli, Muhammad Haiqal (Universiti Teknologi PETRONAS, 2016)
Issues related to conventional energy production such as environmental pollution, high cost of fossil fuels and increase in global energy demand have shifted the global attention towards renewable energy( RE). Hybrid Power System (HPS) consisting of a combination of RE resources can overcome the issues related to energy, as RE sources are clean, infinite, and cost-effective in a long term. Implementation of RE in HPS however is a challenging task. RE technologies have high capital cost for the set up, and energy production from RE is unpredictable due to their stochastic nature. It is therefore important to optimize HPS so that a cost effective design can be achieved. The objective of this paper is to design HPS based on Power Pinch Analysis (PoPA) and Systematic Hierarchical Approach for Resilient Process Screening (SHARPS) intensification strategy. PoPA technique which is Modified Storage Cascade Table (SCT) was used to find the minimum electricity target. Then, the electricity target was used in SHARPS to obtain the cost effective HPS. Based on PoPA and SHARPS technique, a cost-effective HPS result was obtained with a desired payback period of ten years.